2021
DOI: 10.1051/e3sconf/202126901012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of slope aspect on altitudinal pattern of soil C:N:P stoichiometry in alpine forest of Tibet

Abstract: Knowledge of altitudinal patterns in soil C, N and P distribution is important for understanding biogeochemical processes in mountainous forests, yet the influence of slope aspects on soil stoichiometry has been largely neglected in previous studies. In this paper, a total number of 150 topsoil samples at four altitudes (3700, 3900, 4100, 4380 m a.s.l.) on sunny and shady slopes of Sygera mountains in the Southeastern Tibet were collected. Soil C, N and P contents, and pH, were measured. Soil temperature, mois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…In this study, the EC value of the soils ranged from 14 mScm −1 to 630 mScm −1 . Following the soil EC rating suggested by Seifu et al [37], the EC content of the soils in the study area was within the range of moderately saline (8)(9)(10)(11)(12)(13)(14)(15)(16) to strongly saline (>16). Te result indicated that there is no signifcant (P < 0.683) diference in salt accumulation along with increasing elevation.…”
Section: Te Chemical Properties Of Soil 421 Soil Ph and Electrical Co...mentioning
confidence: 77%
See 2 more Smart Citations
“…In this study, the EC value of the soils ranged from 14 mScm −1 to 630 mScm −1 . Following the soil EC rating suggested by Seifu et al [37], the EC content of the soils in the study area was within the range of moderately saline (8)(9)(10)(11)(12)(13)(14)(15)(16) to strongly saline (>16). Te result indicated that there is no signifcant (P < 0.683) diference in salt accumulation along with increasing elevation.…”
Section: Te Chemical Properties Of Soil 421 Soil Ph and Electrical Co...mentioning
confidence: 77%
“…Diferent factors signifcantly infuence the physicochemical properties of the soil. Climatic variations such as increasing rainfall and decreasing temperature along the elevation gradient are the most important factors that have signifcant efects on soil properties [14,15]. Te other most critical forms of soil degradation are depletion of soil quality and soil erosion by water, loss of soil organic matter and reduction in soil biological activity, and increased toxicity due to acidifcation and salinization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation